Hydrogel-filled polycaprolactone composite scaffold as well as preparation method and application thereof
By filling the drug-loading material and gel composite in the polycaprolactone scaffold to form a gradient pore structure, the problems of slow degradation, surface hydrophobicity and single function in the prior art are solved, rapid degradation and effective drug release are achieved, and antibacterial and bone-promoting regeneration effects are enhanced.
Patent Information
- Application Number
- CN202411952688.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing polycaprolactone-based stents and polydopamine-loaded granules have problems such as slow degradation, hydrophobic surface, single function and complex preparation process, making it difficult to effectively release drugs and promote bone repair.
The hydrogel-filled polycaprolactone composite scaffold is used to form a gradient pore structure and a multi-layer pore structure by distributing the drug-loading material and gel composite in the polycaprolactone scaffold matrix, which enhances the antibacterial performance of the scaffold and promotes tissue regeneration ability.
It realizes rapid degradation of the stent and drug release, improves cell adhesion and proliferation ability, enhances antibacterial properties and promotes bone regeneration, and is suitable for the repair and regeneration of bone tissue defects under infection.
Smart Images

Figure CN119770727A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical materials, and in particular relates to a hydrogel-filled polycaprolactone composite material stent and a preparation method and application thereof. Background Art
[0002] In recent years, with the development of bone tissue engineering technology, prostheses prepared by tissue engineering have shown good cartilage repair effects, and there is hope that tissue engineering technology can be used to treat growth plate injuries. Cartilage tissue engineering generally includes scaffolds and active substances. The ideal bone tissue engineering scaffold should have an interconnected porous network structure to provide interconnected channels for cell migration, ion transport, and cell-to-cell interaction. Conventional technologies include foaming, sacrificial template method, freeze-drying method and casting method, etc. 3D printing is also called additive manufacturing technology. Due to its unique and significant advantages in high precision, personalized manufacturing and complex shape construction, 3D printing has penetrated into all walks of life, led innovation, and triggered changes in the global manufacturing industry. 3D printing obtains a three-dimensional entity by stacking raw materials layer by layer on a plane. The porosity and shape of the scaffold can be freely designed, which can well meet the needs of bone tissue engineering.
[0003] Polycaprolactone (PCL) is a commonly used material for 3D printing. It has good biocompatibility, is non-toxic, and is degradable. It also has the function of inducing tissue regeneration and providing a place for cell adhesion, proliferation, and differentiation. It is widely used in the field of medical science. However, due to the hydrophobicity of PCL, the adhesion of the formed scaffold will be affected, and its mechanical structure will be significantly damaged after degradation. The introduction of artificial materials through surface modification, physical doping, chemical grafting, etc. can supplement the characteristics that polycaprolactone does not have. By adjusting its mixed components, the advantages of each component can be maximized, thereby meeting the ideal parameter requirements of bone repair materials. In addition, polydopamine microspheres have a certain drug loading capacity and can be used as a drug carrier for bone tissue engineering technology.
[0004] The existing technologies of bone tissue engineering scaffolds include: Literature [Xu Yingke. Characterization and biocompatibility study of 3D printed polycaprolactone / β-tricalcium phosphate scaffolds loaded with polydopamine microspheres [D]. Hainan Medical College, 2023. DOI: 10.27952 / d.cnki.ghnyx.2023.000017.] reported the preparation of polycaprolactone / β-TCP composite scaffolds loaded with polydopamine microspheres, which can be used as bone repair materials to promote bone repair; Literature [Dong Bo. Research on the repair effect of 3D printed composite scaffolds loaded with FK-16 on infected bone defects [D]. Jilin University, 2024. DOI: 10.27162 / d.cnki.gjlin.2024.005386.] reported that by synthesizing 3D printed hydroxyapatite / polycaprolactone scaffolds with sustainable release of FK-16, bone transplant materials that can be used to effectively repair infected bone defects were obtained. However, the polycaprolactone-based scaffolds and polydopamine drug-loaded particles produced by the above-mentioned prior art generally have the following problems: 1) Polydopamine degrades slowly, making it difficult to effectively release enough drugs to achieve antibacterial and bone-promoting effects; 2) The surface of the polycaprolactone scaffold is too hydrophobic, which is not conducive to cell adhesion and proliferation; 3) The components and functions of the material are relatively simple, making it difficult to achieve good antibacterial and bone regeneration effects; 4) The preparation process is complicated and difficult to industrialize. Summary of the invention
[0005] In order to overcome the problems existing in the above-mentioned prior art, one of the purposes of the present invention is to provide a hydrogel-filled polycaprolactone composite material scaffold. The second purpose of the present invention is to provide a method for preparing the above-mentioned hydrogel-filled polycaprolactone composite material scaffold. The third purpose of the present invention is to provide the application of the above-mentioned hydrogel-filled polycaprolactone composite material scaffold. The gradient pore structure scaffold of the present invention not only has good porosity and biocompatibility, antibacterial properties, and induces osteogenic differentiation of stem cells, but also can accelerate the release of antibacterial drugs, especially in the case of infection, and initiate the slow release of internally encapsulated drugs that promote tissue regeneration and repair, and is suitable for the repair and regeneration of bone tissue defects under infection.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] The first aspect of the present invention provides a hydrogel-filled polycaprolactone composite material stent, comprising a polycaprolactone stent matrix; the surface and interior of the polycaprolactone stent matrix are distributed with interconnected pores, and the pores gradually increase from the surface to the interior of the polycaprolactone stent matrix; a drug-loaded material is distributed in the polycaprolactone stent matrix, and the drug-loaded material comprises mesoporous ceramics, the interior of the mesoporous ceramics is filled with tissue regeneration and repair drugs, and the surface of the mesoporous ceramics is coated with polydopamine; the pores of the polycaprolactone stent matrix are filled with a gel composite material; the gel composite material comprises a hydrogel and a metal organic framework material wrapped in the hydrogel; the interior of the metal organic framework material is loaded with antibacterial drugs.
[0008] The pores of the stent in the present invention gradually increase from the surface to the inside of the polycaprolactone stent matrix, forming gradient pores and a multi-level pore structure, and the porous structure is filled with a gel composite material, wherein the internal pores of the polycaprolactone stent matrix refer to the pores formed by stacking between fibers (macroscopic pores, hundreds of microns), and the external pores of the polycaprolactone stent matrix are the pores formed on the fibers due to pore-forming technology (microscopic pores, several to tens of microns).
[0009] Preferably, the surface of the polycaprolactone composite material has pores with a size of 1-100 μm.
[0010] Preferably, the mesoporous ceramic is selected from at least one of mesoporous silicon, mesoporous calcium silicate, mesoporous magnesium silicate, mesoporous zinc silicate, mesoporous strontium silicate, mesoporous bioglass, and mesoporous hydroxyapatite.
[0011] Preferably, the particle size of the mesoporous ceramic is 30 to 1500 nm.
[0012] Preferably, the specific surface area of the mesoporous ceramic is 100 to 2000 m 2 / g, and the average pore size is 2 to 50 nm.
[0013] Preferably, the metal organic framework material is a zeolite imidazolate framework material self-assembled by coordination of zinc ions and 2-methylimidazole.
[0014] Preferably, the drug promoting tissue regeneration and repair is selected from at least one of bone morphogenetic protein-2, bone morphogenetic protein-7, vascular endothelial cell factor, platelet-derived factor, curcumin, melatonin, alendronate sodium, naringin, resveratrol, dexamethasone, gentamicin sulfate, epidermal growth factor, fibroblast growth factor, keratinocyte growth factor, nerve growth factor, berberine hydrochloride, gentamicin, transforming growth factor, insulin-like growth factor, parathyroid hormone, growth hormone, interleukin, alendronate sodium, salmon calcitonin, zoledronic acid sodium, ibandronate sodium, strontium ranelate, and vitamin D.
[0015] Preferably, the antibacterial drug is at least one of ertapenem, imipenem, meropenem, piperacillin / tazobactam, amikacin, colistin, polymyxin B, amikacin, linezolid, vancomycin, tetracycline, tigecycline, fluorouracil, amphotericin B, caspofungin, voriconazole, triclosan, chlorhexidine, penicillin, roxithromycin, clarithromycin, azithromycin, tobramycin, etimicin, netilmicin, tetracycline, chloramphenicol, ciprofloxacin, levofloxacin, moxifloxacin, metronidazole, ornidazole, tinidazole, itraconazole, mycobacterium, and griseofulvin.
[0016] Preferably, the molecular weight of the polycaprolactone is 30,000 to 100,000 Daltons.
[0017] Preferably, the raw material matrix of the hydrogel is selected from at least one of methacrylated hyaluronic acid, methacrylated silk fibroin, methacrylated chondroitin sulfate, methacrylated chitosan, methacrylated carboxymethyl chitosan, methacrylated gelatin, methacrylated sodium alginate, hyaluronic acid, silk fibroin, chondroitin sulfate, chitosan, carboxymethyl chitosan, gelatin, and sodium alginate.
[0018] The second aspect of the present invention provides a method for preparing the hydrogel-filled polycaprolactone composite material scaffold of the first aspect, comprising the following steps:
[0019] S1. Mixing the drug-carrying material, gluconolactone and polycaprolactone in a solvent to obtain a mixed solution, transferring the solution to a mold and placing the solution for a period of time to obtain a mixed material film; using the mixed material film as a printing material, 3D printing to obtain a scaffold with a gradient pore structure; after printing, immersing the scaffold with a gradient pore structure in water to remove gluconolactone and residual solvent;
[0020] S2. Reacting an antibacterial drug, 2-methylimidazole and a zinc source in water to obtain the metal organic framework material, mixing the metal organic framework material, a hydrogel matrix, a cross-linking agent and the scaffold with a gradient pore structure, and performing photocuring to obtain the hydrogel-filled polycaprolactone composite material scaffold.
[0021] Preferably, the method for preparing the drug-loaded material comprises the following steps: immersing the mesoporous ceramic in a solution containing a drug for promoting tissue regeneration and repair to obtain a mesoporous ceramic encapsulating the drug for promoting tissue regeneration and repair; immersing the mesoporous bioceramic encapsulating the drug for promoting tissue regeneration and repair in a solution containing dopamine to obtain a drug-loaded material.
[0022] More preferably, the solvent of the solution containing the drug for promoting tissue regeneration and repair is water.
[0023] More preferably, the mass ratio of the mesoporous ceramic, the regeneration and repair promoting drug and dopamine is (50-1000):(0.005-10):100.
[0024] Preferably, the mass ratio of the drug-carrying material to polycaprolactone is (0.005-0.05):1.
[0025] Preferably, the mass ratio of gluconolactone to polycaprolactone is (0.5-3):1.
[0026] Preferably, the solvent is dichloromethane.
[0027] Preferably, the process conditions for 3D printing satisfy at least one of the following:
[0028] a) 3D printing uses a printing needle with a diameter of 0.15-0.4mm;
[0029] b) Printing and heating temperature: barrel 60~80℃, needle 60~90℃;
[0030] c) Fiber spacing 0.8mm×0.8mm; printing speed 8~17mm / s;
[0031] d) Air pressure is 320-400Kpa;
[0032] e) The height of the stent layer is 75-95% of the needle diameter;
[0033] f) The fiber orientation is "0-90°".
[0034] The fiber spacing refers to the distance between the mid-axes of adjacent fibers in the horizontal and vertical directions. The fiber orientation refers to the angle between the upper and lower layers of fibers. The support layer height refers to the layer thickness of the printed layers.
[0035] Preferably, in step S1, the mixing time is 50-100 hours.
[0036] More preferably, the mixing is performed under stirring conditions, wherein the stirring rate is 100 to 1000 rpm.
[0037] Preferably, the placement time is 50-100 hours.
[0038] Preferably, the film-forming condition of the mixed material film is volatilization film-forming.
[0039] Preferably, the mass ratio of the 2-methylimidazole, the antibacterial drug and the zinc source is (18-23):(4-10):1.
[0040] Preferably, the zinc source is zinc nitrate.
[0041] Preferably, the hydrogel matrix is selected from at least one of methacryloylated hyaluronic acid, methacryloylated silk fibroin, methacryloylated chondroitin sulfate, methacryloylated chitosan, methacryloylated carboxymethyl chitosan, methacryloylated gelatin, methacryloylated sodium alginate, hyaluronic acid, silk fibroin, chondroitin sulfate, chitosan, carboxymethyl chitosan, gelatin, and sodium alginate.
[0042] Preferably, the step S2 specifically includes the following steps: slowly adding a zinc source to an aqueous solution containing an antibacterial drug and 2-methylimidazole to react to obtain the metal organic framework material; mixing the metal organic framework material, a hydrogel matrix, and a cross-linking agent in a buffer solution to obtain a hydrogel matrix mixed solution; and then adding the scaffold having a gradient pore structure to the hydrogel matrix mixed solution and performing photocuring to obtain the hydrogel-filled polycaprolactone composite material scaffold.
[0043] More preferably, the mass volume ratio of the scaffold with a gradient pore structure to the hydrogel matrix mixed solution is (0.5-1.5) g:10 mL.
[0044] More preferably, the light curing time is 30 to 120 seconds.
[0045] More preferably, the photoinitiator is phenyl-2,4,6-trimethylbenzoyl lithium phosphite.
[0046] More preferably, the buffer solution is PBS solution.
[0047] More preferably, the photocuring is performed using blue light.
[0048] The third aspect of the present invention provides the use of the polycaprolactone composite material scaffold filled with hydrogel in the first aspect in the preparation of a product for promoting bone tissue repair and regeneration.
[0049] The beneficial effects of the present invention are:
[0050] The invention provides a hydrogel-filled polycaprolactone composite material stent, comprising a polycaprolactone composite material stent; the polycaprolactone composite material stent has a porous structure, wherein the pores on the surface and inside are interconnected, and the pore size increases gradually from the surface to the inside, so that the printed stent simultaneously obtains macroscopic large pores (fiber gaps) and microscopic small pores (fiber surface holes), which can not only improve the surface roughness of the stent, achieve the purpose of significantly promoting the adhesion of stent cells, but also significantly increase the specific surface area of the stent, accelerate the degradation of polycaprolactone and release more acidic degradation products, thereby accelerating the degradation of polydopamine and accelerating the release of drugs embedded therein, solving the problem of slow degradation of polydopamine in vivo and in vitro.
[0051] The specific beneficial effects are as follows:
[0052] (1) The pores of the hydrogel-filled polycaprolactone composite material scaffold of the present invention are filled with a gel composite material, the gel composite material includes a hydrogel and a metal organic framework material wrapped in the hydrogel, and the metal organic framework material can enhance the antibacterial properties of the gradient pore structure polycaprolactone scaffold; in the case of bone infection, the pH in the local microenvironment is low, which will significantly accelerate the degradation of the metal organic framework material and accelerate the release of the antibacterial drugs loaded therein, synergistically achieving better antibacterial and bone regeneration effects. In addition, the present invention fills the pores of the printed scaffold with a hydrogel with good hydrophilicity, which can further regulate the hydrophilicity of the material while maintaining the mechanical strength of the material to make it more suitable for the regeneration and repair of bone defects.
[0053] (2) The hydrogel-filled polycaprolactone composite scaffold of the present invention uses drug-loaded mesoporous ceramics as the scaffold forming material, which is further dispersed inside the polycaprolactone, which not only enhances the mechanical strength of the scaffold and the drug-loaded material, making it suitable for bone repair, but also has the effect of sustained and controlled release of drugs.
[0054] (3) The present invention provides a method for preparing the above-mentioned hydrogel-filled polycaprolactone composite material scaffold. The preparation method is simple and feasible. The use of gluconolactone as a pore-forming agent can make the scaffold have a gradient pore structure, so that the printed scaffold can simultaneously obtain macroscopic large pores (fiber gaps) and microscopic small pores (holes on the fiber surface). In addition, gluconolactone is easily soluble in water and can be easily eliminated after the reaction.
[0055] (4) The hydrogel-filled polycaprolactone composite scaffold of the present invention has great application potential in the preparation of products that promote bone tissue repair and regeneration. The surface-modified gradient pore structure scaffold has good porosity and biocompatibility, antibacterial properties, and the characteristics of inducing stem cell osteogenic differentiation. Under infection conditions, the metal organic framework material can accelerate the release of antibacterial drugs and then initiate the slow release of the internally encapsulated drugs that promote tissue regeneration and repair. Therefore, it is suitable for the repair and regeneration of bone tissue defects under infection. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 The release performance of the drug for promoting tissue regeneration and repair in vitro of the materials prepared in the examples and comparative examples;
[0057] Figure 2 The release performance of the drug for promoting tissue regeneration and repair in vitro of the materials prepared in Example 1 and the comparative example;
[0058] Figure 3 The in vitro antimicrobial drug release performance of the materials prepared in the examples and comparative examples;
[0059] Figure 4The in vitro antimicrobial drug release performance of the materials prepared in Example 1 and the comparative example;
[0060] Figure 5 The alkaline phosphatase activity of the scaffolds prepared in the examples and comparative examples. DETAILED DESCRIPTION
[0061] The present invention is further described in detail below through specific examples. The raw materials used in the following examples, unless otherwise specified, can be obtained from conventional commercial sources or prepared and separated by simple synthesis; the processes used, unless otherwise specified, are conventional processes in the art.
[0062] Example 1
[0063] This embodiment provides a hydrogel-filled polycaprolactone composite material scaffold, and the preparation method thereof is as follows:
[0064] S1. At 25°C, 1000 mg of mesoporous bioglass (average particle size between 200 and 1000 nm, specific surface area between 300 and 900 m 2 / g, average pore size between 10nm and 45nm) was dispersed in 100mL aqueous solution (containing 50mg curcumin), stirred at 300rpm for 12h, and freeze-dried; at 20°C, 500mg of the loaded mesoporous material was dispersed in 100mL of 2mg / mL dopamine aqueous solution (pH=8.4), stirred at 200rpm for 16min, and freeze-dried to obtain the polydopamine-wrapped mesoporous material.
[0065] S2. Dissolve 10g of polycaprolactone (molecular weight: 40,000 Daltons) in 100mL of dichloromethane, add 12g of gluconolactone and 1000mg of mesoporous ceramics@polydopamine particles, and stir magnetically at 500rpm for 50h to obtain a gluconolactone / mesoporous ceramics@polydopamine particles / polycaprolactone solution. Pour the solution onto a glass culture dish and place it in a ventilated state for 72h to obtain a gluconolactone / mesoporous ceramics@polydopamine particles / polycaprolactone film.
[0066] S3, put the film into the printing barrel, with a needle diameter of 0.2mm, a barrel temperature of 65℃, a needle temperature of 70℃, a fiber spacing of 0.8mm×0.8mm, a printing rate of 10mm / s, a fiber orientation of "0-90°", an air pressure of 350Kpa, and a scaffold layer height of 80% of the needle diameter, and print the gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold layer by layer. Soak 20mg of gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold in 10mL of aqueous solution, and ultrasonicate at room temperature for 0.5 hours to obtain a gradient pore structure mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold.
[0067] S4. Add 20 mg of vancomycin to 20 mL of 27 mg / mL 2-methylimidazole aqueous solution, add 4 mL of 6.5 mg / mL zinc nitrate aqueous solution while stirring, wash and freeze-dry after reaction to obtain drug-loaded ZIF8. Dissolve 250 mg of methacrylated sodium alginate in 10 mL of PBS solution containing 0.2% phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and then add 200 mg of drug-loaded ZIF8 to obtain a hydrogel solution containing drug-loaded ZIF8. Place 60 mg of bioactive ceramic / polycaprolactone scaffold in the hydrogel solution containing drug-loaded ZIF8, disperse for 2 minutes, take out, and solidify by irradiation with blue light for 60 seconds. Freeze the scaffold in a -20°C refrigerator, and then freeze-dry in a freeze dryer to obtain a drug-loaded ZIF8 hydrogel filled with gradient pore structure drug-loaded mesoporous ceramic @ polydopamine / polycaprolactone scaffold.
[0068] The modified polycaprolactone composite material scaffold prepared in Example 1 is a porous structure filled with a gel composite material. The pores of the scaffold gradually increase from the surface to the inside of the polycaprolactone scaffold matrix, wherein the internal pores of the polycaprolactone scaffold matrix refer to the pores formed by stacking between fibers (macro pores, hundreds of microns), and the external pores of the polycaprolactone scaffold matrix are the pores formed on the fibers due to pore-forming technology (micro pores, several to tens of microns).
[0069] Example 2
[0070] This embodiment provides a hydrogel-filled polycaprolactone composite material scaffold, and the preparation method thereof is as follows:
[0071] S1. At 0°C, 1000 mg of mesoporous silica (average particle size between 30 and 600 nm, specific surface area between 500 and 1800 m 2 / g, with an average pore size between 2nm and 10nm) was dispersed in 100mL of aqueous solution (containing 0.3mg of bone morphogenetic protein-7), stirred at 400rpm for 8h, and freeze-dried; at 0°C, 700mg of the loaded mesoporous material was dispersed in 100mL of 2.8mg / mL dopamine aqueous solution (pH=8.2), stirred at 300rpm for 12min, and freeze-dried to obtain the polydopamine-coated mesoporous material.
[0072] S2. Dissolve 10g polycaprolactone (molecular weight: 60,000 Daltons) in 150mL dichloromethane, add 16g gluconolactone and 800mg mesoporous ceramics@polydopamine particles, and stir magnetically at 400rpm for 40h to obtain a gluconolactone / mesoporous ceramics@polydopamine particles / polycaprolactone solution. Pour the solution onto a glass culture dish and place it in a ventilated state for 60h to obtain a gluconolactone / mesoporous ceramics@polydopamine particles / polycaprolactone film.
[0073] S3, put the film into the printing barrel, with a needle diameter of 0.3mm, a barrel temperature of 70℃, a needle temperature of 75℃, a fiber spacing of 0.8mm×0.8mm, a printing rate of 7mm / s, a fiber orientation of "0-90°", an air pressure of 340Kpa, and a scaffold layer height of 85% of the needle diameter, and print the gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold layer by layer. Soak 20mg of gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold in 25mL of aqueous solution, and ultrasonicate at room temperature for 0.75 hours to obtain a gradient pore structure mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold.
[0074] S4. Add 16 mg of gentamicin to 20 mL of 38 mg / mL 2-methylimidazole aqueous solution, add 2 mL of 18 mg / mL zinc nitrate aqueous solution while stirring, wash and freeze-dry after reaction to obtain drug-loaded ZIF8. Dissolve 200 mg of methacryloyl hyaluronic acid in 10 mL of PBS solution containing 0.3% phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and then add 300 mg of drug-loaded ZIF8 to obtain a hydrogel solution containing drug-loaded ZIF8. Place 100 mg of bioactive ceramic / polycaprolactone scaffold in the hydrogel solution containing drug-loaded ZIF8, disperse for 6 minutes, take out, and solidify by irradiation with blue light for 50 seconds. Freeze the scaffold in a -20°C refrigerator, and then freeze-dry in a freeze dryer to obtain a drug-loaded ZIF8 hydrogel filled with gradient pore structure drug-loaded mesoporous ceramic @ polydopamine / polycaprolactone scaffold.
[0075] Example 3
[0076] This embodiment provides a hydrogel-filled polycaprolactone composite material scaffold, and the preparation method thereof is as follows:
[0077] S1. At 15°C, 1000 mg of mesoporous calcium silicate (average particle size between 1000 and 1200 nm, specific surface area between 200 and 900 m 2 / g, average pore size between 5nm and 15nm) was dispersed in 100mL aqueous solution (containing 40mg alendronate sodium), stirred at 600rpm for 6h, and freeze-dried; at 40°C, 400mg of the loaded mesoporous material was dispersed in 100mL of 1.6mg / mL dopamine aqueous solution (pH=8.6), stirred at 600rpm for 2min, and freeze-dried to obtain the polydopamine-coated mesoporous material.
[0078] S2. Dissolve 10 g of polycaprolactone (molecular weight: 80,000 Daltons) in 250 mL of dichloromethane, add 24 g of gluconolactone and 2200 mg of mesoporous ceramics @ polydopamine particles, and mechanically stir at 600 rpm for 36 h to obtain a gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone solution. Pour the solution onto a glass culture dish and place it in a ventilated state for 96 h to obtain a gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone film.
[0079] S3, put the film into the printing barrel, the needle diameter is 0.45mm, the barrel temperature is 85℃, the needle temperature is 90℃, the fiber spacing is 0.8mm×0.8mm, the printing rate is 10mm / s, the fiber orientation is "0-90°", the air pressure is 400Kpa, and the support layer height is 95% of the needle diameter, and the gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone support is printed layer by layer. 20mg of gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone support was soaked in 50mL of aqueous solution, and ultrasonicated at room temperature for 1 hour to obtain a gradient pore structure mesoporous ceramics @ polydopamine particles / polycaprolactone support.
[0080] S4. Add 40 mg of triclosan to 20 mL of 33 mg / mL 2-methylimidazole aqueous solution, add 3 mL of 10 mg / mL zinc nitrate aqueous solution while stirring, wash and freeze-dry after reaction to obtain drug-loaded ZIF8. Dissolve 100 mg of methacryloyl carboxymethyl gelatin in 10 mL of PBS solution containing 0.15% phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and then add 200 mg of drug-loaded ZIF8 to obtain a hydrogel solution containing drug-loaded ZIF8. Place 150 mg of bioactive ceramic / polycaprolactone scaffold in the hydrogel solution containing drug-loaded ZIF8, disperse for 10 minutes, take out, and solidify by irradiating with blue light for 120 seconds. Freeze the scaffold in a -20°C refrigerator, and then freeze-dry it in a freeze dryer to obtain a drug-loaded ZIF8 hydrogel filled with gradient pore structure drug-loaded mesoporous ceramic @ polydopamine / polycaprolactone scaffold.
[0081] Example 4
[0082] This embodiment provides a hydrogel-filled polycaprolactone composite material scaffold, and the preparation method thereof is as follows:
[0083] S1. At 15°C, 1000 mg of mesoporous calcium silicate (average particle size between 1000 and 1200 nm, specific surface area between 200 and 900 m 2 / g, average pore size between 5nm and 15nm) was dispersed in 100mL aqueous solution (containing 40mg alendronate sodium), stirred at 600rpm for 6h, and freeze-dried; at 40°C, 400mg of the loaded mesoporous material was dispersed in 100mL of 1.6mg / mL dopamine aqueous solution (pH=8.6), stirred at 600rpm for 2min, and freeze-dried to obtain the polydopamine-coated mesoporous material.
[0084] S2. Dissolve 10 g of polycaprolactone (molecular weight: 80,000 Daltons) in 250 mL of dichloromethane, add 24 g of gluconolactone and 2200 mg of mesoporous ceramics @ polydopamine particles, and mechanically stir at 600 rpm for 36 h to obtain a gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone solution. Pour the solution onto a glass culture dish and place it in a ventilated state for 96 h to obtain a gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone film.
[0085] S3, put the film into the printing barrel, the needle diameter is 0.45mm, the barrel temperature is 85℃, the needle temperature is 90℃, the fiber spacing is 0.8mm×0.8mm, the printing rate is 10mm / s, the fiber orientation is "0-90°", the air pressure is 400Kpa, and the support layer height is 95% of the needle diameter, and the gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone support is printed layer by layer. 20mg of gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone support was soaked in 50mL of aqueous solution, and ultrasonicated at room temperature for 1 hour to obtain a gradient pore structure mesoporous ceramics @ polydopamine particles / polycaprolactone support.
[0086] S4. Add 40 mg of triclosan to 20 mL of 33 mg / mL 2-methylimidazole aqueous solution, add 3 mL of 10 mg / mL zinc nitrate aqueous solution while stirring, wash and freeze-dry after reaction to obtain drug-loaded ZIF8. Dissolve 100 mg of methacryloyl carboxymethyl gelatin in 10 mL of PBS solution containing 0.15% phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and then add 200 mg of drug-loaded ZIF8 to obtain a hydrogel solution containing drug-loaded ZIF8. Place 150 mg of bioactive ceramic / polycaprolactone scaffold in the hydrogel solution containing drug-loaded ZIF8, disperse for 10 minutes, take out, and solidify by irradiating with blue light for 120 seconds. Freeze the scaffold in a -20°C refrigerator, and then freeze-dry it in a freeze dryer to obtain a drug-loaded ZIF8 hydrogel filled with gradient pore structure drug-loaded mesoporous ceramic @ polydopamine / polycaprolactone scaffold.
[0087] Comparative Example 1
[0088] This comparative example provides a method for preparing a ZIF8 surface-modified polycaprolactone scaffold, which is substantially the same as Example 1, except that gluconolactone is not used. The specific preparation method is as follows:
[0089] At 25°C, 1000 mg of mesoporous bioglass (average particle size between 200 and 1000 nm, specific surface area between 300 and 900 m 2 / g, average pore size between 10nm and 45nm) was dispersed in 100mL aqueous solution (containing 50mg curcumin), stirred at 300rpm for 12h, and freeze-dried; at 20°C, 500mg of loaded mesoporous material was dispersed in 100mL 2mg / mL dopamine aqueous solution (pH=8.4), stirred at 200rpm for 16min, and freeze-dried to obtain polydopamine-wrapped mesoporous material. 10g polycaprolactone (molecular weight: 40,000 Daltons) was dissolved in 100mL dichloromethane, and 1000mg mesoporous ceramics @ polydopamine particles were added, and magnetic stirring was performed at 500rpm for 50h to obtain a mesoporous ceramics @ polydopamine particles / polycaprolactone solution. The solution was poured onto a glass culture dish and placed under ventilation for 72h to obtain a mesoporous ceramics @ polydopamine particles / polycaprolactone film. The film was placed in a printing barrel, with a needle diameter of 0.2 mm, a barrel temperature of 65 ° C, a needle temperature of 70 ° C, a fiber spacing of 0.8 mm × 0.8 mm, a printing rate of 10 mm / s, a fiber orientation of "0-90 °", an air pressure of 350 Kpa, and a scaffold layer height of 80% of the needle diameter, and the mesoporous ceramic @ polydopamine particles / polycaprolactone scaffold was printed layer by layer. 20 mg of mesoporous ceramic @ polydopamine particles / polycaprolactone scaffold was soaked in 10 mL of aqueous solution, and ultrasonicated at room temperature for 0.5 hours to obtain a mesoporous ceramic @ polydopamine particles / polycaprolactone scaffold. 20 mg of vancomycin was added to 20 mL of 27 mg / mL 2-methylimidazole aqueous solution, and 4 mL of 6.5 mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, it was washed and freeze-dried to obtain drug-loaded ZIF8. Dissolve 250 mg of methacrylated sodium alginate in 10 mL of PBS solution containing 0.2% phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and then add 200 mg of drug-loaded ZIF8 to obtain a hydrogel solution containing drug-loaded ZIF8. Place 60 mg of bioactive ceramic / polycaprolactone scaffold in the hydrogel solution containing drug-loaded ZIF8, disperse for 2 minutes, take it out, and solidify it by irradiating with blue light for 60 seconds. Freeze the scaffold in a -20°C refrigerator, and then freeze-dry it in a freeze dryer to obtain a drug-loaded ZIF8 hydrogel filled with drug-loaded mesoporous ceramic@polydopamine / polycaprolactone scaffold.
[0090] The modified polycaprolactone composite material stent prepared in Comparative Example 1 has a relatively smooth surface, with occasional holes ranging from a few microns to tens of microns.
[0091] Comparative Example 2
[0092] This comparative example provides a preparation method of a polycaprolactone scaffold with a gradient pore structure, which is substantially the same as Example 1, except that: no surface modification of ZIF8 is performed. The preparation method is specifically as follows:
[0093] At 25°C, 1000 mg of mesoporous bioglass (average particle size between 200 and 1000 nm, specific surface area between 300 and 900 m 2 / g, average pore size between 10nm and 45nm) was dispersed in 100mL aqueous solution (containing 50mg curcumin), stirred at 300rpm for 12h, and freeze-dried; at 20℃, 500mg of loaded mesoporous material was dispersed in 100mL 2mg / mL dopamine aqueous solution (pH=8.4), stirred at 200rpm for 16min, and freeze-dried to obtain polydopamine-wrapped mesoporous material. 10g polycaprolactone (molecular weight: 40,000 Daltons) was dissolved in 100mL dichloromethane, and then 12g gluconolactone and 1000mg mesoporous ceramics @ polydopamine particles were added, and magnetic stirring was carried out at 500rpm for 50h to obtain gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone solution. The solution was poured on a glass culture dish and placed in a ventilated state for 72h to obtain gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone film. The film was placed in a printing barrel, with a needle diameter of 0.2 mm, a barrel temperature of 65 ° C, a needle temperature of 70 ° C, a fiber spacing of 0.8 mm × 0.8 mm, a printing rate of 10 mm / s, a fiber orientation of "0-90 °", an air pressure of 350 Kpa, and a scaffold layer height of 80% of the needle diameter, and gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone scaffolds were printed layer by layer. 20 mg of gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone scaffolds were soaked in 10 mL of aqueous solution and ultrasonicated at room temperature for 0.5 hours to obtain gradient pore structure mesoporous ceramics @ polydopamine particles / polycaprolactone scaffolds. 60 mg of bioactive ceramics / polycaprolactone scaffolds were placed in a hydrogel solution containing 20 mg of vancomycin, dispersed for 2 minutes, and then taken out and cured by irradiation with blue light for 60 seconds. The scaffold was placed in a -20°C refrigerator for freezing, and then freeze-dried in a freeze dryer to obtain a drug-loaded mesoporous ceramic @ polydopamine / polycaprolactone scaffold with a gradient pore structure filled with drug-loaded hydrogel.
[0094] Comparative Example 3
[0095] This comparative example provides a method for preparing a polycaprolactone stent, which is substantially the same as Example 1, except that: ZIF8 is not loaded with drugs. The specific preparation method is as follows:
[0096] At 25°C, 1000 mg of mesoporous bioglass (average particle size between 200 and 1000 nm, specific surface area between 300 and 900 m 2 / g, average pore size between 10nm and 45nm) was dispersed in 100mL aqueous solution (containing 50mg curcumin), stirred at 300rpm for 12h, and freeze-dried; at 20℃, 500mg of loaded mesoporous material was dispersed in 100mL 2mg / mL dopamine aqueous solution (pH=8.4), stirred at 200rpm for 16min, and freeze-dried to obtain polydopamine-wrapped mesoporous material. 10g polycaprolactone (molecular weight: 40,000 Daltons) was dissolved in 100mL dichloromethane, and then 12g gluconolactone and 1000mg mesoporous ceramics @ polydopamine particles were added, and magnetic stirring was carried out at 500rpm for 50h to obtain gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone solution. The solution was poured on a glass culture dish and placed in a ventilated state for 72h to obtain gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone film. The film was placed in a printing barrel, with a needle diameter of 0.2 mm, a barrel temperature of 65 ° C, a needle temperature of 70 ° C, a fiber spacing of 0.8 mm × 0.8 mm, a printing rate of 10 mm / s, a fiber orientation of "0-90 °", an air pressure of 350 Kpa, and a scaffold layer height of 80% of the needle diameter, and gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone scaffolds were printed layer by layer. 20 mg of gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone scaffolds were soaked in 10 mL of aqueous solution and ultrasonicated at room temperature for 0.5 hours to obtain gradient pore structure mesoporous ceramics @ polydopamine particles / polycaprolactone scaffolds. 4 mL of 6.5 mg / mL zinc nitrate aqueous solution was added dropwise to 20 mL of 27 mg / mL 2-methylimidazole aqueous solution while stirring, and washed and freeze-dried after the reaction to obtain ZIF8. Dissolve 250 mg of methacryloyl sodium alginate in 10 mL of PBS solution containing 0.2% phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and then add 200 mg of ZIF8 to obtain a hydrogel solution containing ZIF8. Place 60 mg of bioactive ceramic / polycaprolactone scaffold in the hydrogel solution containing ZIF8, disperse for 2 minutes, take it out, and solidify it by irradiating with blue light for 60 seconds. Freeze the scaffold in a -20°C refrigerator, and then freeze-dry it in a freeze dryer to obtain a ZIF8 hydrogel-filled gradient pore structure drug-loaded mesoporous ceramic @ polydopamine / polycaprolactone scaffold.
[0097] Comparative Example 4
[0098] This comparative example provides a preparation method of a polycaprolactone stent, which is substantially the same as Example 1, except that it does not contain drug-loaded ZIF8. The specific preparation method is as follows:
[0099] At 25°C, 1000 mg of mesoporous bioglass (average particle size between 200 and 1000 nm, specific surface area between 300 and 900 m 2 / g, average pore size between 10nm and 45nm) was dispersed in 100mL aqueous solution (containing 50mg curcumin), stirred at 300rpm for 12h, and freeze-dried; at 20℃, 500mg of loaded mesoporous material was dispersed in 100mL 2mg / mL dopamine aqueous solution (pH=8.4), stirred at 200rpm for 16min, and freeze-dried to obtain polydopamine-wrapped mesoporous material. 10g polycaprolactone (molecular weight: 40,000 Daltons) was dissolved in 100mL dichloromethane, and then 12g gluconolactone and 1000mg mesoporous ceramics @ polydopamine particles were added, and magnetic stirring was carried out at 500rpm for 50h to obtain gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone solution. The solution was poured on a glass culture dish and placed in a ventilated state for 72h to obtain gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone film. The film was placed in a printing barrel, with a needle diameter of 0.2 mm, a barrel temperature of 65 ° C, a needle temperature of 70 ° C, a fiber spacing of 0.8 mm × 0.8 mm, a printing rate of 10 mm / s, a fiber orientation of "0-90 °", an air pressure of 350 Kpa, and a scaffold layer height of 80% of the needle diameter, and gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone scaffolds were printed layer by layer. 20 mg of gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone scaffolds were soaked in 10 mL of aqueous solution and ultrasonicated at room temperature for 0.5 hours to obtain a gradient pore structure mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold. 250 mg of methacrylated sodium alginate was dissolved in 10 mL of PBS solution containing 0.2% phenyl-2,4,6-trimethylbenzoyl lithium phosphite to obtain a hydrogel solution. 60 mg of bioactive ceramic / polycaprolactone scaffold was placed in the hydrogel solution, dispersed for 2 minutes, and then taken out and solidified by irradiation with blue light for 60 seconds. The scaffold was frozen in a -20°C refrigerator, and then freeze-dried in a freeze dryer to obtain a hydrogel-filled gradient pore structure drug-loaded mesoporous ceramic@polydopamine / polycaprolactone scaffold.
[0100] Comparative Example 5
[0101] This comparative example provides a method for preparing a polycaprolactone stent, which is substantially the same as Example 1, except that: the bioactive ceramic@polydopamine particles are not loaded with drugs. The specific preparation method is as follows:
[0102] At 25°C, 1000 mg of mesoporous bioglass (average particle size between 200 and 1000 nm, specific surface area between 300 and 900 m 2 / g, average pore size between 10nm and 45nm) was dispersed in 100mL aqueous solution, stirred at 300rpm for 12h, and freeze-dried; at 20°C, 500mg of mesoporous material was dispersed in 100mL of 2mg / mL dopamine aqueous solution (pH=8.4), stirred at 200rpm for 16min, and freeze-dried to obtain polydopamine-wrapped mesoporous material. 10g of polycaprolactone (molecular weight: 40,000 Daltons) was dissolved in 100mL of dichloromethane, and then 12g of gluconolactone and 1000mg of mesoporous ceramics @ polydopamine particles were added, and magnetic stirring was carried out at 500rpm for 50h to obtain gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone solution. The solution was poured on a glass culture dish and placed in a ventilated state for 72h to obtain a gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone film. The film was placed in a printing barrel, with a needle diameter of 0.2 mm, a barrel temperature of 65 ° C, a needle temperature of 70 ° C, a fiber spacing of 0.8 mm × 0.8 mm, a printing rate of 10 mm / s, a fiber orientation of "0-90 °", an air pressure of 350 Kpa, and a scaffold layer height of 80% of the needle diameter, and gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone scaffolds were printed layer by layer. 20 mg of gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone scaffolds were soaked in 10 mL of aqueous solution and ultrasonicated at room temperature for 0.5 hours to obtain gradient pore structure mesoporous ceramics @ polydopamine particles / polycaprolactone scaffolds. 20 mg of vancomycin was added to 20 mL of 27 mg / mL 2-methylimidazole aqueous solution, and 4 mL of 6.5 mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, it was washed and freeze-dried to obtain drug-loaded ZIF8. Dissolve 250 mg of methacryloyl sodium alginate in 10 mL of PBS solution containing 0.2% phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and then add 200 mg of drug-loaded ZIF8 to obtain a hydrogel solution containing drug-loaded ZIF8. Place 60 mg of bioactive ceramic / polycaprolactone scaffold in the hydrogel solution containing drug-loaded ZIF8, disperse for 2 minutes, take it out, and solidify it by irradiating with blue light for 60 seconds. Freeze the scaffold in a -20°C refrigerator, and then freeze-dry it in a freeze dryer to obtain a drug-loaded ZIF8 hydrogel filled with a gradient pore structure mesoporous ceramic @ polydopamine / polycaprolactone scaffold.
[0103] Comparative Example 6
[0104] This comparative example provides a method for preparing a polycaprolactone stent, which is substantially the same as Example 1, except that the drug-loaded polydopamine particles do not contain bioactive ceramics. The specific preparation method is as follows:
[0105] At 20°C, 50 mg of curcumin was dispersed in 100 mL of 2 mg / mL dopamine aqueous solution (pH = 8.4), stirred at 200 rpm for 16 min, and freeze-dried to obtain drug-loaded polydopamine particles. 10 g of polycaprolactone (molecular weight: 40,000 Daltons) was dissolved in 100 mL of dichloromethane, and then 12 g of gluconolactone and 1000 mg of drug-loaded polydopamine particles were added, and magnetic stirring was performed at 500 rpm for 50 h to obtain a gluconolactone / drug-loaded polydopamine particles / polycaprolactone solution. The solution was poured onto a glass culture dish and placed under ventilation for 72 h to obtain a gluconolactone / drug-loaded polydopamine particles / polycaprolactone film. The film was placed in a printing barrel, with a needle diameter of 0.2 mm, a barrel temperature of 65 ° C, a needle temperature of 70 ° C, a fiber spacing of 0.8 mm × 0.8 mm, a printing rate of 10 mm / s, a fiber orientation of "0-90 °", an air pressure of 350 Kpa, and a scaffold layer height of 80% of the needle diameter, and gluconolactone / drug-loaded polydopamine particles / polycaprolactone scaffolds were printed layer by layer. 20 mg of gluconolactone / drug-loaded polydopamine particles / polycaprolactone scaffolds were soaked in 10 mL of aqueous solution, and ultrasonicated at room temperature for 0.5 hours to obtain gradient pore structure drug-loaded polydopamine particles / polycaprolactone scaffolds. 20 mg of vancomycin was added to 20 mL of 27 mg / mL 2-methylimidazole aqueous solution, and 4 mL of 6.5 mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, it was washed and freeze-dried to obtain drug-loaded ZIF8. Dissolve 250 mg of methacryloyl sodium alginate in 10 mL of PBS solution containing 0.2% phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and then add 200 mg of drug-loaded ZIF8 to obtain a hydrogel solution containing drug-loaded ZIF8. Place 60 mg of drug-loaded polydopamine particles / polycaprolactone scaffolds in the hydrogel solution containing drug-loaded ZIF8, disperse for 2 minutes, take out, and solidify by irradiating with blue light for 60 seconds. Freeze the scaffold in a -20°C refrigerator, and then freeze-dry in a freeze dryer to obtain a drug-loaded ZIF8 hydrogel filled with gradient pore structure drug-loaded polydopamine particles / polycaprolactone scaffolds.
[0106] Comparative Example 7
[0107] This comparative example provides a method for preparing a polycaprolactone scaffold, which is substantially the same as Example 1, except that it does not contain polydopamine. The specific preparation method is as follows:
[0108] At 25°C, 1000 mg of mesoporous bioglass (average particle size between 200 and 1000 nm, specific surface area between 300 and 900 m 2 / g, average pore size between 10nm and 45nm) was dispersed in 100mL aqueous solution (containing 50mg curcumin), stirred at 300rpm for 12h, and freeze-dried to obtain drug-loaded mesoporous ceramics. 10g polycaprolactone (molecular weight: 40,000 Daltons) was dissolved in 100mL dichloromethane, and then 12g gluconolactone and 1000mg drug-loaded mesoporous ceramics were added, and magnetic stirring was carried out at 500rpm for 50h to obtain gluconolactone / drug-loaded mesoporous ceramics / polycaprolactone solution. The solution was poured on a glass culture dish and placed in a ventilated state for 72h to obtain a gluconolactone / drug-loaded mesoporous ceramic / polycaprolactone film. The film was placed in a printing barrel, with a needle diameter of 0.2 mm, a barrel temperature of 65 ° C, a needle temperature of 70 ° C, a fiber spacing of 0.8 mm × 0.8 mm, a printing rate of 10 mm / s, a fiber orientation of "0-90 °", an air pressure of 350 Kpa, and a scaffold layer height of 80% of the needle diameter, and gluconolactone / drug-loaded mesoporous ceramics / polycaprolactone scaffolds were printed layer by layer. 20 mg of gluconolactone / drug-loaded mesoporous ceramics / polycaprolactone scaffolds were soaked in 10 mL of aqueous solution and ultrasonicated at room temperature for 0.5 hours to obtain gradient pore structure drug-loaded mesoporous ceramics / polycaprolactone scaffolds. 20 mg of vancomycin was added to 20 mL of 27 mg / mL 2-methylimidazole aqueous solution, and 4 mL of 6.5 mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, it was washed and freeze-dried to obtain drug-loaded ZIF8. Dissolve 250 mg of methacrylated sodium alginate in 10 mL of PBS solution containing 0.2% phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and then add 200 mg of drug-loaded ZIF8 to obtain a hydrogel solution containing drug-loaded ZIF8. Place 60 mg of bioactive ceramic / polycaprolactone scaffold in the hydrogel solution containing drug-loaded ZIF8, disperse for 2 minutes, take it out, and solidify it by irradiating with blue light for 60 seconds. Freeze the scaffold in a -20°C refrigerator, and then freeze-dry it in a freeze dryer to obtain a drug-loaded ZIF8 hydrogel filled with a gradient pore structure drug-loaded mesoporous ceramic / polycaprolactone scaffold.
[0109] Comparative Example 8
[0110] This comparative example provides a method for preparing a polycaprolactone stent, which is substantially the same as Example 1, except that it does not contain drug-loaded mesoporous ceramic@polydopamine particles. The specific preparation method is as follows:
[0111] Dissolve 10g polycaprolactone (molecular weight: 40,000 Daltons) in 100mL dichloromethane, add 12g gluconolactone, stir magnetically at 500rpm for 50h to obtain a gluconolactone / polycaprolactone solution. Pour the solution onto a glass petri dish and place it under ventilation for 72h to obtain a gluconolactone / polycaprolactone film. Put the film into a printing barrel, with a needle diameter of 0.2mm, a barrel temperature of 65℃, a needle temperature of 70℃, a fiber spacing of 0.8mm×0.8mm, a printing rate of 10mm / s, a fiber orientation of "0-90°", an air pressure of 350Kpa, and a scaffold layer height of 80% of the needle diameter, and print the gluconolactone / polycaprolactone scaffold layer by layer. Soak 20mg of the gluconolactone / polycaprolactone scaffold in 10mL of aqueous solution and ultrasonicate at room temperature for 0.5h to obtain a polycaprolactone scaffold with a gradient pore structure. 20 mg of vancomycin was added to 20 mL of 27 mg / mL 2-methylimidazole aqueous solution, and 4 mL of 6.5 mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, the mixture was washed and freeze-dried to obtain drug-loaded ZIF8. 250 mg of methacrylated sodium alginate was dissolved in 10 mL of PBS solution containing 0.2% phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and then 200 mg of drug-loaded ZIF8 was added to obtain a hydrogel solution containing drug-loaded ZIF8. 60 mg of gradient pore structure polycaprolactone scaffold was placed in the hydrogel solution containing drug-loaded ZIF8, dispersed for 2 minutes, and then taken out and solidified by irradiation with blue light for 60 seconds. The scaffold was frozen in a -20°C refrigerator, and then freeze-dried in a freeze dryer to obtain a drug-loaded ZIF8 hydrogel filled with gradient pore structure polycaprolactone scaffold.
[0112] Comparative Example 9
[0113] This comparative example provides a preparation method of a polycaprolactone stent, which is substantially the same as Example 1, except that it does not contain drug-loaded mesoporous ceramic@polydopamine particles, gluconolactone and drug-loaded ZIF8. The specific preparation method is as follows:
[0114] 10g of polycaprolactone (molecular weight: 40,000 Daltons) was placed in the printing barrel, with a needle diameter of 0.2mm, a barrel temperature of 65℃, a needle temperature of 70℃, a fiber spacing of 0.8mm×0.8mm, a printing rate of 10mm / s, a fiber orientation of "0-90°", an air pressure of 350Kpa, and a scaffold layer height of 80% of the needle diameter, and the gluconolactone / polycaprolactone scaffold was printed layer by layer. 20mg of the gluconolactone / polycaprolactone scaffold was soaked in 10mL of aqueous solution and ultrasonicated at room temperature for 0.5 hours to obtain a polycaprolactone scaffold with a gradient pore structure. 250mg of methacrylated sodium alginate was dissolved in 10mL of PBS solution containing 0.2% phenyl-2,4,6-trimethylbenzoyl lithium phosphite to obtain a hydrogel solution. 60mg of the polycaprolactone scaffold with a gradient pore structure was placed in the hydrogel solution, dispersed for 2min, and then taken out and cured by irradiation with blue light for 60s. The scaffold was placed in a -20°C refrigerator for freezing, and then freeze-dried in a freeze dryer to obtain a hydrogel-filled polycaprolactone scaffold.
[0115] Experimental analysis
[0116] The scaffold materials prepared in the examples and comparative examples were evaluated for their performance as follows: Figures 1-2 and Tables 1 to 3.
[0117] 1. In vitro cytotoxicity evaluation
[0118] The prepared gel was evaluated and scored according to the requirements of GB / T 16886.5.
[0119] L929 mouse fibroblasts that had been cultured for 24 hours and were growing vigorously were digested and prepared to a density of 1.0×10 5 100 μL / mL was inoculated in a 96-well plate. After the cells grew into a monolayer, the original culture medium was removed and 100 μL of the test sample extract, blank control solution, positive control solution and negative control solution were added respectively, with 6 replicates in each group. After the addition of samples, the 96-well plate was placed in a 37°C, 5% CO2 incubator for 24 hours.
[0120] After 24 hours of culture, the original culture medium was aspirated, and 50 μL of MTT (1 mg / mL) was added to each well. The culture was continued for 2 hours. After the end, the supernatant was aspirated and 100 μL of 99.5% pure isopropanol was added to dissolve the crystals; the absorbance value was measured on an ELISA instrument with 570 nm as the main absorption wavelength and 650 nm as the reference wavelength to calculate the cell survival rate.
[0121] The cell viability was calculated according to the following formula: Cell viability (%) = 100 × OD 570e / OD570 b
[0122] OD 570eIt is the average optical density of the test sample or control sample extract.
[0123] OD 570b is the average optical density of the blank.
[0124] The experimental results are shown in Table 1:
[0125] Table 1 In vitro cell survival rate of the scaffolds prepared in the examples and comparative examples
[0126]
[0127] 2. Hemolytic performance test
[0128] Blood was collected from the heart of healthy rabbits according to the amount of blood used in the experiment. For example, 10 mL of blood was collected, and 0.5 mL of potassium oxalate solution with a mass concentration of 20 g / L was added to prepare fresh anticoagulated rabbit blood. Take 8 mL of fresh anticoagulated rabbit blood and dilute it with 10 mL of sodium chloride injection with a mass concentration of 9 g / L. The test sample group was added with the test sample according to the extraction ratio, and then 10 mL of sodium chloride injection was added; 10 mL of sodium chloride was added to each tube of the negative control group; 10 mL of distilled water was added to each tube of the positive control group. Three tubes were operated in parallel for each group. After all the test tubes were placed in a constant temperature water bath at (37±1)℃ for 30 minutes, 0.2 mL of diluted rabbit blood was added to each test tube, gently mixed, and placed in a (37±1)℃ water bath for another 60 minutes. Pour out the liquid in the tube and centrifuge at 800g for 5 minutes. Aspirate the supernatant and transfer it to a cuvette, and measure the absorbance at a wavelength of 545 nm using a spectrophotometer. The absorbance of the test group and the control group is the average of the three tubes. The absorbance of the negative control tube should not be greater than 0.03; the absorbance of the positive control tube should be 0.8±0.3, otherwise the test should be repeated. Calculate according to the following formula: Hemolysis rate = (absorbance of the test group - absorbance of the negative control group) / (absorbance of the positive control group - absorbance of the negative control group) × 100%, the results are shown in Table 2:
[0129] Table 2 Hemolysis rate of materials obtained in Examples and Comparative Examples
[0130]
[0131] From the hemolysis rate evaluation results of the examples and comparative examples (Table 2), it can be seen that the hemolysis rate of the hydrogel prepared by the method of the present invention is less than 5%, and there is no hemolysis risk.
[0132] 3. In vitro drug release performance test
[0133] The in vitro drug release performance evaluation method is as follows: 500 mg of the product is immersed in 200 mL of PBS (pH = 7.4) in a constant temperature shaker at 37°C and 60 rpm, the test solution is collected regularly, and an equal amount of PBS is supplemented. The content of the therapeutic agent in the collected test solution is determined by high performance liquid chromatography (HPLC), and compared with the total amount of the therapeutic agent loaded in the product, the cumulative release rate of the therapeutic agent is calculated.
[0134] The results of in vitro testing of drug release performance for promoting tissue regeneration and repair are shown in Figure 1 and 2 , the release period of various drugs for promoting tissue regeneration and repair prepared by the scaffolds in Examples 1 to 4 exceeds 5 weeks. Comparative Example 1 does not use gluconolactone, and its scaffold fiber does not contain a porous structure. Its drug release rate is significantly lower than that of Example 1, and the release period is significantly longer; Comparative Examples 2 and 4 do not contain ZIF8, and the drug-loaded polydopamine particles in Comparative Example 6 do not contain bioactive ceramics, which has little effect on the release of drugs, and the release curves are close to those of Example 1. Comparative Example 7 does not contain polydopamine, and the burst release is significantly increased compared with Example 1, and the release rate is significantly accelerated, and the release is basically completed in 5 weeks.
[0135] The results of in vitro antimicrobial drug release performance test are shown in Figure 3 and 4 , the release period of various antibacterial drugs for the stents prepared in Examples 1 to 4 exceeds 3 weeks. Comparative Example 1 does not use gluconolactone, and its stent fiber does not contain a porous structure, and its antibacterial drug release rate is close to that of Example 1; compared with Example 1, the changes in Comparative Examples 5 to 8 have little effect on the release of antibacterial drugs embedded on the stent surface, and the release curves are also close to that of Example 1; in Comparative Example 2, the antibacterial drugs are not encapsulated by ZIF8, and the antibacterial drugs are directly dispersed in the hydrogel. Compared with Example 1, the burst release is significantly increased, and the release rate is significantly accelerated, and the release is basically completed in 2 weeks.
[0136] 4. In vitro osteogenic differentiation test of preosteoblasts
[0137] The composite materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were irradiated and sterilized, and then immersed in DMEM basal culture medium at a concentration of 10 mg / mL, and placed in a 37°C shaker at 120 rpm for 24 hours. After the extraction, the mixture of the composite material and the culture medium was centrifuged at 1000 rpm and the supernatant was collected. The collected extracts were diluted 2 times with the corresponding DMEM culture medium, and finally 10% fetal bovine serum was added to obtain a conditioned medium.
[0138] MC3T3-E1 cells were plated at 1×10 5The cells were inoculated in a 24-well plate at a density of 100 μg / mL. After 24 hours of adherent culture, the conditioned medium was replaced and cultured in an incubator at 37°C and 5% carbon dioxide atmosphere. The culture medium was replaced every 2-3 days. After 7 days of culture, the osteogenic differentiation performance of MC3T3-E1 cells was detected by the alkaline phosphatase secreted by them and measured by the pNPP method. The specific steps are as follows: After the cells were washed with PBS solution, they were immersed in a PBS solution containing 0.1 mol / L glycine, 1 mmol / L magnesium chloride and 0.05% Triton X-100 (octoxynol). After the cells were dissolved, the dissolved solution was evenly mixed with disodium p-nitrophenyl phosphate, and the mixed solution was placed at 37°C for 30 minutes. Subsequently, the mixed solution was added dropwise to a 96-well plate, and the absorbance of each well at a wavelength of 405 nm was measured using an ELISA reader.
[0139] Definition of alkaline phosphatase activity unit: In diethanolamine (DEA) buffer at pH 9.8, at 37°C, the amount of alkaline phosphatase required to hydrolyze para-nitrophenyl phosphate chromogenic substrate to produce 1 micromole of p-nitrophenol per minute is defined as one enzyme activity unit, also known as one DEA enzyme activity unit. In glycine buffer at pH 9.6, at 25°C, the amount of alkaline phosphatase required to hydrolyze para-nitrophenyl phosphate chromogenic substrate to produce 1 micromole of p-nitrophenol per minute is defined as one enzyme activity unit, also known as one Glycine enzyme activity unit. One Glycine enzyme activity unit is approximately equivalent to 3 DEA enzyme activity units. According to the definition of enzyme activity, calculate the alkaline phosphatase activity in the sample and plot it separately, as shown below. Figure 3 shown.
[0140] Depend on Figure 5It can be seen that the scaffolds in Examples 1 to 4 of the present invention have a good effect of inducing cells to secrete alkaline phosphatase, but in the case of not using gluconolactone, Comparative Example 1 does not have a gradient pore structure, and its cell activity is not as good as that with a gradient pore structure, which also affects the cell secretion of alkaline phosphatase, and the alkaline phosphatase activity is slightly reduced compared with Example 1. Comparative Example 3 is not loaded with antibacterial drugs, and the alkaline phosphatase activity is close to that of Example 1. The drug-loaded polydopamine particles in Comparative Example 6 do not contain bioactive ceramics, which also affects the cell secretion of alkaline phosphatase, and the alkaline phosphatase activity is also slightly reduced compared with Example 1. Comparative Examples 2 and 4 do not contain ZIF8 particles with good biological activity, and the alkaline phosphatase activity is significantly reduced compared with Example 1. Comparative Example 7 does not contain polydopamine with osteogenic activity, but at the same time, the release of the drug is significantly accelerated, which also affects the cell secretion of alkaline phosphatase, and the alkaline phosphatase activity is also significantly reduced compared with Example 1. The bioactive ceramic / polydopamine particles in Comparative Example 5 were not loaded with drugs, and the alkaline phosphatase activity was significantly decreased compared with Example 1. Comparative Example 8 did not contain drug-loaded bioactive ceramic / polydopamine particles, and the alkaline phosphatase activity was significantly decreased compared with Example 1, and its alkaline phosphatase activity was lower than that of Comparative Example 5. Comparative Example 9 contained neither ZIF8 with good biological activity, nor gradient pore structure, drug-loaded mesoporous ceramic@polydopamine particles, and antibacterial drugs, and its alkaline phosphatase activity was the lowest.
[0141] 5. Antibacterial performance test of stent
[0142] Take fresh slant cultures of Staphylococcus aureus and Escherichia coli, count the live bacteria in the bacterial suspension, and prepare a diluent (1% peptone in 0.03 mol / L PBS (pH = 7.2-7.4)) to a bacterial count of 5 × 10 5 ~10×10 6 cfu / mL of bacterial suspension. Place the samples in sterile plates, add 50μL of bacterial suspension to each sample, record the time of adding bacteria to each tube, inoculate the blood plate 60min after adding bacteria, and place the samples in a 5mL nutrient broth tube. Incubate the blood plate and broth tube inoculated with bacteria at 37℃ for 48h, observe the preliminary results, and continue to culture in the sterile growth tube until the 28th day. If the broth tube is turbid and the blood plate has bacterial growth, it is recorded as positive, indicated by (+); if it is still clear on the 35th day, it is considered as sterile growth, indicated by (–).
[0143] Table 3 Antibacterial effect of the stents prepared in the examples and comparative examples
[0144]
[0145] As shown in Table 3, the composite scaffolds prepared in Examples 1 to 4 of the present invention and Comparative Examples 1, 5 to 8 all have good long-term antibacterial effects and can grow aseptically for 35 days. Comparative Examples 2, 3, 4 and 9 do not contain ZIF8 or antibacterial drugs and do not have antibacterial effects.
[0146] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.
Claims
1. A hydrogel-filled polycaprolactone composite material scaffold, characterized in that: It includes a polycaprolactone stent matrix; the surface and interior of the polycaprolactone stent matrix are distributed with interconnected pores, and the pores gradually increase from the surface to the interior of the polycaprolactone stent matrix; drug-loaded materials are distributed in the polycaprolactone stent matrix, and the drug-loaded materials include mesoporous ceramics, the interior of the mesoporous ceramics is filled with tissue regeneration and repair drugs, and the surface of the mesoporous ceramics is coated with polydopamine; the pores of the polycaprolactone stent matrix are filled with gel composite materials; the gel composite materials include hydrogel and a metal organic framework material wrapped in the hydrogel; the interior of the metal organic framework material is loaded with antibacterial drugs.
2. The hydrogel-filled polycaprolactone composite material scaffold according to claim 1, characterized in that: The surface of the polycaprolactone composite material has holes with a size of 1-100 μm.
3. The hydrogel-filled polycaprolactone composite material scaffold according to claim 1, characterized in that: The mesoporous ceramic is selected from at least one of mesoporous silicon, mesoporous calcium silicate, mesoporous magnesium silicate, mesoporous zinc silicate, mesoporous strontium silicate, mesoporous bioglass, and mesoporous hydroxyapatite; And / or, the raw material matrix of the hydrogel is selected from at least one of methacryloylated hyaluronic acid, methacryloylated silk fibroin, methacryloylated chondroitin sulfate, methacryloylated chitosan, methacryloylated carboxymethyl chitosan, methacryloylated gelatin, methacryloylated sodium alginate, hyaluronic acid, silk fibroin, chondroitin sulfate, chitosan, carboxymethyl chitosan, gelatin, and sodium alginate.
4. The method for preparing the hydrogel-filled polycaprolactone composite material scaffold according to any one of claims 1 to 3, characterized in that: The steps include: S1. Mixing the drug-carrying material, gluconolactone and polycaprolactone in a solvent to obtain a mixed solution, transferring the solution to a mold and placing the solution for a period of time to obtain a mixed material film; using the mixed material film as a printing material, 3D printing to obtain a scaffold with a gradient pore structure; After printing, the scaffold with gradient pore structure was immersed in water to remove gluconolactone and residual solvent; S2. Reacting an antibacterial drug, 2-methylimidazole and a zinc source in water to obtain the metal organic framework material, mixing the metal organic framework material, a hydrogel matrix, a cross-linking agent and the scaffold with a gradient pore structure, and performing photocuring to obtain the hydrogel-filled polycaprolactone composite material scaffold.
5. The method for preparing the hydrogel-filled polycaprolactone composite material scaffold according to claim 4, characterized in that: The preparation method of the drug-carrying material comprises the following steps: immersing the mesoporous ceramic in a solution containing a drug for promoting tissue regeneration and repair to obtain a mesoporous ceramic encapsulating the drug for promoting tissue regeneration and repair; immersing the mesoporous bioceramic encapsulating the drug for promoting tissue regeneration and repair in a solution containing dopamine to obtain a drug-carrying material.
6. The method for preparing the hydrogel-filled polycaprolactone composite material scaffold according to claim 4, characterized in that: The mass ratio of the drug-carrying material to polycaprolactone is (0.005-0.05):
1. And / or, the mass ratio of gluconolactone to polycaprolactone is (0.5-3):
1.
7. The method for preparing the hydrogel-filled polycaprolactone composite material scaffold according to claim 4, characterized in that: The process conditions of the 3D printing meet at least one of the following: a) 3D printing uses a printing needle with a diameter of 0.15-0.4mm; b) Printing and heating temperature: barrel 60~80℃, needle 60~90℃; c) Fiber spacing 0.8mm×0.8mm; printing speed 8~17mm / s; d) Air pressure is 320-400Kpa; e) The height of the stent layer is 75-95% of the needle diameter.
8. The method for preparing the hydrogel-filled polycaprolactone composite material scaffold according to claim 4, characterized in that: In step S1, the mixing time is 50-100 hours; And / or, the placement time is 50-100h.
9. The method for preparing the hydrogel-filled polycaprolactone composite material scaffold according to claim 4, characterized in that: The mass ratio of the 2-methylimidazole, the antibacterial drug and the zinc source is (18-23):(4-10):1; And / or, the zinc source is zinc nitrate.
10. Use of the hydrogel-filled polycaprolactone composite material scaffold according to any one of claims 1 to 3 in the preparation of products for promoting bone tissue repair and regeneration.
Citation Information
Patent Citations
Multifunctional nano drug-loaded system and preparation method thereof
CN106581674A
Microsphere hydrogel scaffold and preparation method and application thereof
CN112755253A
Regenerative bone scaffold as well as preparation method and application thereof
CN118924949A
Method for producing hydroxyapatite-bioglass materials, said materials and products thereof
US20230084724A1